2017
DOI: 10.18357/jcs.v42i1.16882
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Play at Home and in Kindergarten and Grade One: Parents’ Perceptions

Abstract: Christine Portier is a postdoctoral fellow in the Department of Curriculum, Teaching, and Learning at OISE/University of Toronto. She is a former elementary teacher who now teaches graduate courses in elementary education and conducts research on young children's oral language and writing in play contexts in northern rural and Indigenous communities.Adam Murray worked as a teacher in the city centre for Edmonton Public School Board for ten years. He is currently the principal of Kennedy Elementary School and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Incidentally, parents' perception of play seems to be in line with the literature on free play which states that play should be fun and enjoyable, and that children should be given the choice to select their play activity or materials (Bergen & Fromberg, 2010;Bullard, 2017;Fisher, 2008;Howard, 2010). However, parents did not mention other possible types of play and their importance in the early years, and their role in children's play (Howard, 2010;Peterson et al, 2017;Pyle et al, 2018). For example, these parents could either be unaware of guided play, or misconstrued guided play to be drill-and-practice or rote-learning (Bubikova-Moan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Incidentally, parents' perception of play seems to be in line with the literature on free play which states that play should be fun and enjoyable, and that children should be given the choice to select their play activity or materials (Bergen & Fromberg, 2010;Bullard, 2017;Fisher, 2008;Howard, 2010). However, parents did not mention other possible types of play and their importance in the early years, and their role in children's play (Howard, 2010;Peterson et al, 2017;Pyle et al, 2018). For example, these parents could either be unaware of guided play, or misconstrued guided play to be drill-and-practice or rote-learning (Bubikova-Moan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These studies found that teachers with higher professional training in early childhood care and education (ECCE) were able to perceive play and learning occurring simultaneously. Hence, it is possible that parents without professional training in ECCE could lack an understanding or possess a misconception about play and learning in the early years (Howard, 2010;IPA, 2010;Peterson et al, 2017, Pyle et al, 2020. Hence, as mentioned previously, it is vital to organise a variety of appropriate programmes for parents to help them understand the relationship between play and learning in the early years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One primary parental concern about play is that it is idle, unstructured and unconstructive. While competing studies have found differing results in terms of categories of parents who tend to embrace this idea, it remains a view that recurs in studies of parents’ perceptions of play (Brooker, 2010; Peterson et al, 2017; Kane, 2016; Little et al, 2011). Some scholars have found that vulnerable groups such as ethnic minority communities more consistently report concern over the idleness of play (Brooker, 2010; Chowdhury and Rivalland, 2012).…”
Section: Play Anxietymentioning
confidence: 99%